1987
DOI: 10.1111/1540-6229.00439
|View full text |Cite
|
Sign up to set email alerts
|

The Affordability of Adequate Housing

Abstract: A "quality-based" measure of housing affordability problems employing the cost of housing just meeting adequacy standards is proposed as an improvement over the conventional "high" rent-to-income criterion. Based on "Annual Housing Survey" data, affordability difficulties grew between 1975 and 1983 by either measure. The conventional measure, however, overestimated the extent of quality-based affordability difficulty for renters by 20% in 1975 and 24% in 1983 based upon Section 8 housing quality standards. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 3 publications
2
34
0
Order By: Relevance
“…This was due to the lower socioeconomic standing among blacks and Hispanics. Besides that, studies carried out by [24], [19], [1], [4] and [21] also found that different ethnic groups and races faced differing housing costs due to their differing socioeconomic status. This study on the other hand, revealed that variables such as household structure, type of work, level of education, type of housing, household income and household expenditure on housing costs and non-housing costs do not have significant influences on rent arrears prevailing amongst tenants in MBI public housing.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…This was due to the lower socioeconomic standing among blacks and Hispanics. Besides that, studies carried out by [24], [19], [1], [4] and [21] also found that different ethnic groups and races faced differing housing costs due to their differing socioeconomic status. This study on the other hand, revealed that variables such as household structure, type of work, level of education, type of housing, household income and household expenditure on housing costs and non-housing costs do not have significant influences on rent arrears prevailing amongst tenants in MBI public housing.…”
Section: Resultsmentioning
confidence: 98%
“…Lower income households and high housing costs entitle them to housing benefits. Households have to occupy small sized and low quality dwellings as trade-offs for their lack of affordability in obtaining suitable housing [21,28]. Various methods have been introduced by past researchers to measure housing affordability levels among households which are generally used to analyse the financial ability displayed by households [23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been mainly the housing sector on that theoretical considerations have been executed (see Lerman/Reeder 1987;Stone 1990Stone , 1993Stone , 2006Hancock 1993;Chaplin/Freeman 1999;Thalmann 1999Thalmann , 2003Kutty 2005;Lux 2007). Only in recent years these considerations have also been applied -to a very modest extent -to utility markets.…”
Section: Introductionmentioning
confidence: 99%